Accessibility and sustainable use of Urban Green Areas as a factor for environmental preservation - Vasconcelos, Francisca Dalila Menezes; Mota, Francisco Suetonio Bastos; Menescal, Larissa de Miranda (Revista Nacional de Gerenciamento de Cidades, 2021)
The accessibility of Urban Green Areas (UGA) is widely studied in terms of parameters and metrics. The present work aims to analyze the relationship of accessibility and use of Urban Green Areas with the environmental preservation of these areas. To this end, a bibliographic survey of the existing indexes and indicators of accessibility of existing UGA was first carried out, resulting in 14 scientific papers analyzed. Then, three UGA of the city of Fortaleza were selected to analyze the relationship between accessibility and environmental preservation. It was found that areas without accessibility and sustainable use showed a higher degree of environmental degradation when compared to areas that had some kind of use or accessibility by residents.